2012
DOI: 10.1007/s10792-012-9531-7
|View full text |Cite
|
Sign up to set email alerts
|

Actinomyces canaliculitis and its surgical treatment

Abstract: The objective of this article is to describe four rare cases of Actinomyces israelii canaliculitis and their surgical treatment in a case series consisting of four cases of Actinomyces israelii canaliculitis. Patient charts were reviewed retrospectively. All four patients presented with epiphora, recurrent conjunctivitis, swelling around the superior canaliculus, and mucopurulent punctal discharge persisting despite medical treatments. Two patients with large canalicular dilation were treated with canaliculopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 7 publications
3
16
0
3
Order By: Relevance
“…Since topical or systemic antibiotic treatment is not effective, the most adequate treatment for canaliculitis is thought to be surgical treatment. 3 In the present case, we performed only punctoplasty and removal of the concretion, because the patient had severe dry eye. Her punctum was obstructed spontaneously several weeks after the procedure and required no further treatment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since topical or systemic antibiotic treatment is not effective, the most adequate treatment for canaliculitis is thought to be surgical treatment. 3 In the present case, we performed only punctoplasty and removal of the concretion, because the patient had severe dry eye. Her punctum was obstructed spontaneously several weeks after the procedure and required no further treatment.…”
Section: Discussionmentioning
confidence: 91%
“…The most effective treatment for canaliculitis is surgical extraction of the bacterial concretion. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…Of these, the most common infection is postoperative endophthalmitis after an ocular procedure, where A. neuii (164)(165)(166), A. meyeri (167), and "A. viscosus" (168) have been detected, while in cases of endogenous endophthalmitis, which is far less common, A. neuii (169) and A. israelii (170) have been detected. A. israelii has also been isolated from cases of postoperative keratitis (171) and primary infections of the lacrimal duct, i.e., canaliculitis (172)(173)(174). In addition, A. meyeri and A. georgiae have been found in specimens from cases of canaliculitis (172,175), while A. naeslundii was identified in a swab specimen taken from a cornea after trauma leading to keratitis (107).…”
Section: Eye Infectionsmentioning
confidence: 99%
“…Pediatric canaliculitis is uncommon, and a review of the available English literature showed only 11 previous cases, the findings of which are tabulated in Table 1 . [ 1 3 4 5 6 7 8 9 10 ]…”
Section: Discussionmentioning
confidence: 99%